The effect of ageing on chemical and strength characteristics of nanoclay-modified bitumen and asphalt mixture - Omar H.A.; Katman H.Y.; Bilema M.; Ahmed M.K.A.; Milad A.; Md Yusoff N.I. (MDPI AG, 2023)
This study was conducted to investigate the effect of ageing on bitumen, before and after modification. Nano-clay modified bitumen (NCMB) was produced by adding nano-clay (NC) to 60/70 penetration grade bitumen; then, the binder was tested using conventional tests for properties such as penetration, softening point and viscosity. These tests were carried out on the modified binder before and after ageing. A rolling thin film oven (RTFO) was used to simulate short-term ageing (STA), and a pressure ageing vessel (PAV) was used to simulate long-term ageing (LTA) for the modified binder. After initial results showed an improvement for the modified bitumen regarding the effect of ageing, the investigation continued using Fourier transform infrared spectroscopy (FTIR), where the microstructure distribution of the modified binder before and after ageing was observed. Finally, there was no doubt that the effect of ageing on mixtures should be investigated. For this step, the indirect tensile strength (ITS) test, which highlights the strength changes that occur for the mixtures after ageing, was selected. The results indicated that the tensile strength of mixtures made with modified bitumen showed better resistance against ageing when NC was added, which is in good agreement with the results of previous binder tests. The results of this study show that the modification of bitumen using nano-clay as an additive improves the ageing resistance of the binder, which is consequently reflected in the strength of the asphalt mixture. 2021 by the authors. Licensee MDPI, Basel, Switzerland.